2013
DOI: 10.1080/13549839.2013.857647
|View full text |Cite
|
Sign up to set email alerts
|

Space for equity: socioeconomic variations in the provision of public parks in Hermosillo, Mexico

Abstract: This article examines the intersection between globalisation and allocation of open public space by testing the spatial equity hypothesis in Hermosillo, Mexico, a regional city impacted directly by global processes. Availability and accessibility of public parks were examined using a geographic information system and neighbourhoods were stratified into quintiles based on socioeconomic status. Overall, the analysis shows that the amount of public park space in Hermosillo is substandard and its distribution reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 51 publications
(66 reference statements)
0
13
0
5
Order By: Relevance
“…Contrasting results also emerged for Shanghai, with more studies finding inequity for green space proximity [81,82,91,98] than equity [99]. Three studies in Latin American cities (Santiago de Chile; Hermosillo, Mexico; Bogotá, Colombia) [18,38,80], and three other studies in African cities (Cairo, Egypt; Cape Town, South Africa) [21,86,96] found that high-SES people live closer to parks than low-SES people.…”
Section: Results: Do Inequities In the Global South Vary Based On Geomentioning
confidence: 84%
See 2 more Smart Citations
“…Contrasting results also emerged for Shanghai, with more studies finding inequity for green space proximity [81,82,91,98] than equity [99]. Three studies in Latin American cities (Santiago de Chile; Hermosillo, Mexico; Bogotá, Colombia) [18,38,80], and three other studies in African cities (Cairo, Egypt; Cape Town, South Africa) [21,86,96] found that high-SES people live closer to parks than low-SES people.…”
Section: Results: Do Inequities In the Global South Vary Based On Geomentioning
confidence: 84%
“…Studies in other Asian cities such as Sheikhupura, Pakistan [69], Tehran, Iran [71,84], and Hamadan, Iran [46] also found inequitable results for green space quantity. All sampled articles that measured quantity in Latin America [18,20,72,73] and Africa [21,77,85,89,96] discovered inequities. Effect sizes for inequities were particularly large in some studies that measured green space area per capita [21,73,85].…”
Section: Results: Do Inequities In the Global South Vary Based On Geomentioning
confidence: 99%
See 1 more Smart Citation
“…Reported definitions of spatial equity were classified into one of the four themes identified in the ‘Methods’ section (Online Supplemental Material). Overall, the themes appear mutually exclusive, with only Lara-Valencia and García-Pérez 26 referring to both distributional fairness (Theme 1) and causes of spatial inequity (Theme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies referred to spatial equity as the fairness of the distribution of both benefits and burdens. 20,22,2628 Five further studies suggested that resource distributions and access should be fair. 23,24,2931 One study was set in the context of environmental health, referring to spatial equity as a the fair distribution of hazards.…”
Section: Resultsmentioning
confidence: 99%